MODEL KINETIKA PERUBAHAN WARNA LABEL INDIKATOR DARI KLOROFIL DAUN SINGKONG (MANIHOT ESCULENTA CRANTZ) - Eddwina Aidila Fitria, Endang Warsiki, dan Indah Yuliasih (Jurnal Teknologi Industri Pertanian, 2017)
Time Temperature Indicators (TTI) is a smart packaging that  important for consumers to know the appropriateness of product through an indicator colour change. Currently, there is no development of the kinetics models at TTI to give information for users about the relationship between colour change indicator and time storage. The objective of this research was to develop a kinetic model of smart label. This label was made from chitosan and PVA were added by chlorophyll extracted from cassava leaves. Indicator label stored at five storage temperatures to check the label performance at temperatures of freezer (-10±2°C), refrigerator (2±3oC), air conditioning  (17±2oC), room (25±2oC), and hot temperature (50oC). Parameter was observed in the colour change at the label is the value of ohue which show the real colour.The results showed that label indicator changed colour from green to brown. The changes of colour indicator label wouldldarker when stored at high temperatures.The kinetic model of chlorophyll discolouration was developed by Arrhenius equation using ordo 0 and ordo 1. The plot of ln k value and 1/T has resulted on the equation for kinetic model discolouration label the values of k = 9.22.1010 e -15294,7/T with activation energy of 15.2947 kkal/mol for ordo 0 and k = 1.81.1012 e -19891,9/T with activation energy of 19.8919 kkal/mol for ordo 1. The model could predict the quality change of some product accordance with the kinetic model.Keywords : kinetic model, smart label, chlorophyll